Autograft ossiculoplasty in cholesteatoma surgery: a histological study. (October 2014) - Attanasio, Giuseppe; Gaudio, Eugenio; Mammola, Caterina L.; Cagnoni, Laura; De Seta, Daniele; Minni, Antonio; Covelli, Edoardo; Filipo, Roberto
Abstract Conclusion: The results of the present study reject the hypothesis that epithelial inclusions into the ossicles could cause cholesteatoma recurrences, but strongly suggest the performance of a safe cleaning procedure for ossicular remnants to make them usable in ossiculoplasty in patients with partially or non-encapsulated cholesteatoma. Objective: The aim of the study was to define, before any sort of cleaning procedure, if there is any epithelial inclusion inside the ossicles of patients with cholesteatoma and if the findings could be correlated with surgical aspect of cholesteatoma. Methods: The specimens used for this study comprised 19 mallei and 15 incudes, which were obtained intraoperatively from 24 patients. Each ossicle was grouped on the basis of the intraoperative aspect of the cholesteatoma as follows. Grade 1: 10 ossicles obtained from encapsulated cholestatoma, non-invasive, easily cleavable. Grade 2: 14 ossicles obtained from partially encapsulated cholesteatoma, non-invasive, not easily cleavable. Grade 3: 10 ossicles obtained from non-encapsulated cholesteatoma, invasive, not cleavable. Two stapes and one malleus were taken from patients who underwent middle ear surgery for conductive hearing loss and were used as controls. The ossicles were examined histopathologically after removal. Results: Our results do not show any epithelial inclusion inside the ossicles independently from the macroscopic aspect or growing aggressiveness of cholesteatoma. In addition there was no infiltration of inflammatory cells in grade 1, but it was present in one incus (7.1%) of grade 2 and in five ossicles (50%) of grade 3. In ossicles of grade 3 up to four layers of epithelial cells were found on the surface of the ossicles.